STRUKTUR SEMANTIK VERBA DAN NOMINA PADA KOSAKATA TARI BALI - System, Administrator; -, Putu Devi Maharani; -, Komang Dian Puspita Candra (Sphota : Jurnal Linguistik dan Sastra, 2016)
ABSTRACT   This study is focused on investigating the Balinese dance lexicon, especially for the verbs and nouns, based on Natural Semantic Metalanguage. This study is a qualitative research design. The data was collected through observation, interviews, and note taking. The method used in this research is descriptive qualitative. For the analysis, semantic primes of natural Semantic Metalanguage theory are applied. The data analysis based on the following data classification, semantic structure analysis and components mapping to find out meaning configuration. The research result shows that semantic primes are very helpful and powerful to describe unwell-known lexicon in specific genre of language use in some lexicon in Balinese dance, especially in verb and noun. . Keywords: Natural Semantic Metalanguage, verb, noun, Balinese dancing, lexicon